Sufi Education in “Het Boek Van Bonang”: A Philosophical Perspective on Islamic Education - Waluyo; Djam’anuri; Mufrod Teguh Mulyo (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2023)
This study aims to explain Sufi education in Het Boek Van Bonang using a philosophy of education approach. The three major questions in this study are: the nature of the text; how Sufism appears in Sunan Bonang's text; and the value it contains. This study shows that the text discusses Sufism education, which is a form of Sunan Bonang's criticism of the developing Sufism teachings. Sunan Bonang's teaching is in accordance with Imam Ghazali's Sufism education, namely sunni Sufism (khuluqi amali); this teaching criticizes the concept of wahdatul wujud in Sufism philosophy. Sunni Sufism education leads to becoming Allah's beloved through the path of rijalulllah, while philosophical Sufism leads to becoming Allah's beloved through the path of understanding. The difference between the two lies in the path to Allah. In general, Sunni Sufism is in accordance with the sharia path to Allah. The similarity between philosophical Sufism and Sunni Sufism education is in the aspect of karomah, where both Sufism teachings accept the concept of karomah in its implementation.